Demonstration of the role of the DnaK chaperone system in assembly of 30S ribosomal subunits using a purified in vitro system - MAKI, JENNIFER A. (Copyright 2003 by RNA Society, 2003)
Recently, there has been controversy regarding the ability of the DnaK chaperone system to facilitate Escherichia coli 30S subunit assembly at otherwise nonpermissive conditions. Here, we present additional data indicating that purified DnaK chaperone assembled 30S subunits are functional. Additionally, explanations for reported differences are discussed.